Regular factorizations and perturbation analysis for the core inverse of linear operators in Hilbert spaces. Issue 10 (3rd October 2019) - Huang, Qianglian; Chen, Saijie; Guo, Zhirong; Zhu, Lanping
ABSTRACT: This paper concerns the regular factorization and expression of the core inverse in a Hilbert space. Utilizing the regular factorization, we first give some characterizations for the existence and the expression of the group inverse and core inverse. Based on these, we prove that the core inverse of the perturbed operator has the simplest possible expression if and only if the perturbation is range-preserving, and derive an explicit expression under the rank-preserving perturbation. Thus we can conclude that both the range-preserving perturbation and the rank-preserving perturbation are all continuous perturbations. The obtained results extend and improve many recent ones in matrix theory and operator theory.